Still life [compact disc, unabridged] - Penny, Louise (Penny, Louise. Three Pines mystery, 2014)
Chief Inspector Armand Gamache and his team of investigators are called in to the scene of a suspicious death in a rural village south of Montreal. Jane Neal, a local fixture in the tiny hamlet of Three Pines, just north of the U.S. border, has been found dead in the woods. The locals are certain it's just a tragic hunting accident, but Gamache knows something isn't quite right, and is soon certain that Jane Neal died at the hands of someone much more sinister than a careless hunter.